Side impact beam - Maram, Mohammad; Tami, Qabaha (My University, 2019)
Abstract – This project examines the traumatic shocks experienced by cars during accidents and the fact that the side of the car is one of the most important areas in terms of safety and protection features. Therefore, this study showed the damage to the vehicle, the protection means available and its efficiency, in addition to the quantity of energy absorbed, which is directly proportional to the potential damage to the external structure and thus the passengers so it was necessary to improve the structure of the side of the car by putting some energy absorption materials in doors, columns and bars Sub-frame, roof and seats. These side materials increase the stiffness of the doors to absorb and distribute energy and thus reduce the impact. All this was done by using the number of pieces with different shapes are changed with the type of material used During this study, a simple experiment was carried out to identify which species are best absorbed in energy In addition to using the program (aboqus), finit elemnt .